Effectiveness Of Team-Based Training Programs In Hospitals - Abdul Azis; Laura Lahindah (Green Publisher Indonesia, 2024)
The Effectiveness of Team-Based Training Programs in Hospitals aims to evaluate the effectiveness of team-based training programs in developing the competencies of health workers in hospitals. The research is based on the importance of collaboration between health professions to improve quality of care, but is often hampered by communication and coordination gaps. The research methodology involved systematically evaluating the training program qualitatively, measuring changes in trainees' competencies, and exploring participants' perceptions and experiences. The main objectives of the study were to evaluate the effectiveness of the program in developing health worker competencies, measure changes in participant competencies, explore participant perceptions and experiences, and provide recommendations for future program improvements. It is expected to provide valuable insights into the effectiveness of team-based training programs and identify areas that require improvement. This will be used to improve future training programs, with the ultimate goal of improving health worker collaboration and the quality of health services for patients. The implications of this study include contributions to human resource development in healthcare and the promotion of a culture of collaboration between healthcare professionals. The research findings from the study on the Effectiveness of Team-Based Training Programs in Hospitals indicate several positive outcomes. First, participants reported improvements in communication, particularly in emergency situations, where teams responded more swiftly and effectively. The program also led to enhanced coordination between shifts, reducing errors in patient care and improving the overall quality of services provided